Commercial city building games as pedagogical tools: what have we learned?. Issue 2 (15th March 2023) - Bereitschaft, Bradley
ABSTRACT: This paper presents a review of the literature on the use of commercially available city building games (CBGs), such as SimCity and Cities: Skylines, as learning tools in classroom instruction. Given the ubiquity and popularity of digital games, particularly among young people, instructors in a variety of fields and at various academic levels have begun to consider using these media to motivate and advance student learning. CBGs challenge students to design and build economically viable virtual cities; a task expected to promote systems and critical thinking, as well as the acquisition and use of knowledge regarding urban geography, politics, and planning. Overall, the findings thus far are primarily positive, and suggest that commercial CBGs can be used to address a variety of learning objectives. For geography in particular, CBGs have demonstrated potential in helping students understand and apply geographic concepts, as well as develop spatial reasoning and creativity. In the concluding sections I propose an agenda for future work examining the role and effectiveness of CBGs in pedagogy, and provide a set of recommendations for instructors looking to use CBGs in the classroom.